The Strategic Blowback Paradox: Information Securitization and Israeli Media Control In The Iranian AI-Era Conflict - Muhammad Althaf Alfazian Syahran; Imam Fadhil Nugraha (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2026)
This article analyses the paradoxical outcomes of Israel’s media securitization during the 2025-2026 escalating conflict with Iran, which argues that a strategy designed to maintain its national security additionally created the strategic vulnerabilities Israel aimed to minimize. This article examines how Israel’s Rising Lion Directive formally elevated media access from a regulatory concern into a domain of existential security, by focusing on securitization theory as defined through constructivist epistemology, specifically Buzan, Wæver, and de Wilde speech act framework and Thierry Balzacq reformulation of securitization as a game of legitimation alongside with Armin Krishnan’s Fifth Generation Warfare study. The article analyzes three interconnected elements of this dynamic through qualitative library research and descriptive-analytical interpretation of primary and secondary material covering from 2025-2026. From its historical foundations to its extensive implementation in the Rising Lion Directive, it first traces the historical development of Israel’s censorship regime. Second, it explores how Israel’s international legitimacy was gradually contested by the enforcement of the directive and politicization by the far-right government, weakening the consent and justification pillars that Balzacq argues are essential to sustained securitization. Third, it illustrates how the resulting information vacuum allowed Iran to propagate AI-generated misinformation in the absence of Israel’s independent verification infrastructure on an unprecedented scale. Hence, this article concludes that unilateral information control is not equivalent to narrative dominance in AI-era warfare and that the Israel-Iran conflict represents a notable illustration of strategic blowback in which a state’s information security policy produced outcomes that were contrary to its statedgoals.